MEDB-32. Reducing treatment-related toxicity for children with WNT-activated medulloblastoma. (3rd June 2022) - Taylor, Jessica; Toker, Joseph; Masih, Katherine; Nathan, Erica; Terranova, Sabrina; Gilbertson, Richard
Abstract: WNT-medulloblastoma has an excellent prognosis, with an overall survival rate of 90% among children receiving standard-of-care (SOC) surgical resection, radiotherapy, and chemotherapy. Unfortunately, while curative, this treatment is associated with major, long-term, debilitating motor, developmental, and neuroendocrine side effects. Therefore, it is crucial we develop effective, less toxic therapies for these children. Similarities have been demonstrated between cancer cell lysosomes and those of patients with Niemann-Pick, a lysosomal storage disease characterised by lysosomal fragility and sphingomyelin accumulation. A class of drugs known as Functional Inhibitors of Acid Sphingomyelinase (FIASMAs), increase lysosomal sphingomyelin and destabilise the cancer cell's more fragile lysosomal membrane which leads to the induction of cell-death pathways via lysosomal membrane permeabilisation. Loratadine, an antihistamine with high FIASMA activity, consistently induced lysosomal membrane permeabilisation, leading to increased cell-death, in our panel of mouse and human WNT-medulloblastoma lines. Loratadine exhibited no detrimental effect on normal mouse embryonic stem cells from the lower rhombic lip – the putative cell of origin in WNT-medulloblastoma. Luciferase-expressing mouse WNT-medulloblastoma cells were orthotopically implanted into CD1-nude mice and monitored for tumour development via bioluminescent imaging. Upon tumour engraftment, mice were subjected to reduced SOC (radiotherapy and adjuvant vincristine) plus a clinically relevant dose of loratadine. Response and survival were compared to mice treated with full SOC (radiotherapy, vincristine, cisplatin, and etoposide). Mice treated with 2mg/kg/day of loratadine following reduced SOC demonstrated increased survival when compared to those treated with full SOC (p=0.02) along with a significant reduction in weight loss during treatment (p=<0.0001). This work suggests that loratadine, or other FIASMA compounds, may be good alternative adjuvant therapies for WNT-medulloblastoma. Using less toxic adjuvants could improve long-term outcomes through reducing therapeutic related toxicities for children with this devastating disease.